The relationship between neutrophil percentage-to-albumin ratio and slow and normal coronary flow phenomenon - Renlin Yin; Wei Zhu; Weihai Chen; Jun Shen; Yanming Wu; Zhiming Wang (BMC Cardiovascular Disorders)
Abstract Background The relationship between several inflammatory biomarkers and slow coronary flow phenomenon(SCFP) has been reported. However, the correlation between neutrophil percentage-to-albumin ratio (NPAR) and SCFP is lacking. In this study, we aimed to assess the relationship between NPAR and SCFP. Methods A total of 228 patients were enrolled in this study according to the diagnostic and exclusion criteria. 76 patients were included in the SCFP group, and 152 age-matched patients were included in the normal coronary flow (NCF) group. The baseline data, laboratory parameters and coronary angiography were recorded and compared. Results The values of NPAR were significantly higher in the SCFP group than those in the NCF group (1.78[1.58,1.88] vs. 1.42[1.24,1.66], P < 0.001). NPAR elevated as the number of vessels involved SCFP increased. In the multiple logistic regression tests, NPAR was an independent predictor of SCFP (OR: 1.239, 95%CI: 1.124–1.367, p < 0.001). The receiver operating characteristic curve analysis showed that the cutoff value of NPAR for predicting SCFP was > 1.57 with a 76.3% sensitivity and 67.1% specificity [the area under the curve (AUC) = 0.727, 95%CI: 0.659–0.795, p < 0.001]. NPAR had a better predictive value of SCFP than neutrophil percentage, but not albumin. Conclusion Elevated NPAR may be an independent and valuable predictor of SCFP.